Design of Power Distribution on Operator Control Unit (OCU) Rhino Robot - Ahmad Nur Riza; Imam Arifin; Mahardhika Pratama; Ayyasy Az Zurqi (IPTEK Journal of Proceedings Series, 2019)
OCU Rhino Robot contains from some components with voltage supply requirement was different. Design power distribution was required in this system to provide voltage what correspond with requirement. Using battery what it installed in OCU, so need to display indicator for knowing battery condition. For doing charging process, previously batter must to remove battery from device. So need to made charging system concept what it can make it easier user. Result from this design, knowing that device can operated about 4 hours and 44 minutes. Obtained rating SoC value in 0 – 107% with voltage 16.35VDC when battery was full and 11.9VDC when battery was empty. The value could use as reference at developing charging system on OCU in the next version